Struktur Geologi Bawah Permukaan Pegunungan Selatan Jawa Barat Ditafsir dari Anomali Bouguer - Subagio, Subagio (Jurnal Geologi dan Sumberdaya Mineral, 2018)
West Java Southern Mountain Bouguer Anomaly Pattern indicated subsurface geological structures, characterized by high anomaly gradient patterns, mainly along south coast. The anomaly gradients are about 4-8 mGal/km, that are reflected normal fault  as along as south coast. High anomaly around Ciletuh, Sukabumi shows 240 mGals, while in the northern area is 10 mGals. The high anomaly is interpreted ultramafic outcrop at Ciletuh and the Moho level is at about 13 kms under sea level, while low anomaly in northern  indicates sedimentary basin, which is partly covered by Quartenary volcanic rocks. The geological structures were affected by the collision of the Indian Ocean Plate and the Eurasian Continent Plate. The active faults controlls negative potential (damage, geological hazard), while faults related to Quaternary volcanoes controlled the formation of geothermal traps.Keywords : Bouguer anomaly, Southern Mountain of West Java, high anomaly gradient, normal faults, sediment basins,  geological hazard, geothermal traps.